CFD investigation on the effect of varying fire sprinkler orientation on sprinkler activation time - Nasif, M.S. (Asian Research Publishing Network, 2016)
Water sprinkler system is considered one of the main water-based fire suppression systems. Due to the turbulent nature of fire, prediction of water sprinklers activation time required performing numerous experiments and tests to understand the nature of the parameters involved in changing the activation time. It was noticed that the angle where the sprinkler arms are oriented towards the hot gas jet resulting from a fire had a great impact on the activation time of the sprinkler. In this research the orientation of the sprinkler's arm was changed by using Computational Fluid Dynamics (CFD) simulation. It was found that changing the sprinkler arm angle from perpendicular to the flow (90°) to 60°, 30° and parallel to the flow (0°) has resulted in increasing t sprinkler activation time by about 8, 84, and 163 respectively. The effect of sprinkler activation time variation was investigated on stacked wood pallets heat release rate. It was found that with a parallel orientation the fire is allowed to grow 2.5 times more in terms of Heat Release Rate (HRR) than with perpendicular orientation. © 2006-2016 Asian Research Publishing Network (ARPN).